(untitled) (Journal of the College of Basic Education, 2024)
This current study (in Aesthetic of sculpture formation in using gravel) is considered one of the circulation studies in modern art formation through development and contemporary intellectual connotation. The researchers could not find a direct study on this subject.The researcher dealt with four chapters as following: First Chapter: research problem and its importance and limits in addition to terms definition.The research aims to reveal the artistic characteristics used to employ gravel in fine art.Demonstrating the creative ability in shaping this material.Research problem: in modern time ,fine arts artists achieve many artistic experiences using different raw materials, natural materials and artificial materials that is sued currently and other some are not in classical past eras. Whereas in current age, the artist uses the gravel in individual and unique form.The researcher finds a necessity to make a summarized study on the nature of gravel included in specialized artistic works as mentioned in research title.Importance of research: the researcher finds necessity in studying the material of gravel in standards and aesthetics of formation that explore creative aspects in this material.Research targets: exploring the aesthetics of sculpture formation in gravel. Limitation of time and location: time: 1980 – 2000 Location: all countries globally. Subjectivity: knowing the aesthetic values in formation of gravel material.